Specificity of the connexin W3/4 locus for functional gap junction formation. Issue 6 (1st November 2016) - Xu, Qin; Lin, Xianming; Matiukas, Arvydas; Zhang, Xian; Veenstra, Richard D.
ABSTRACT: The N-terminal (NT) domain of the connexins forms an essential transjunctional voltage (Vj ) sensor and pore-forming domain that when truncated, tagged, or mutated often leads to formation of a nonfunctional channel. The NT domain is relatively conserved among the connexins though the α- and δ-group connexins possess a G2 residue not found in the β- and γ-group connexins. Deletion of the connexin40 G2 residue (Cx40G2Δ) affected the Vj gating, increased the single channel conductance (γj ), and decreased the relative K + /Cl − permeability (PK /PCl ) ratio of the Cx40 gap junction channel. The conserved α/β-group connexin D2/3 and W3/4 loci are postulated to anchor the NT domain within the pore via hydrophilic and hydrophobic interactions with adjacent connexin T5 and M34 residues. Cx40D3N and D3R mutations produced limited function with progressive reductions in Vj gating and noisy low γj gap junction channels that reduced the γj of wild-type Cx40 channels from 150 pS to < 50 pS when coexpressed. Surprisingly, hydrophobic Cx40 W4F and W4Y substitution mutations were not compatible with function despite their ability to form gap junction plaques. These data are consistent with minor and major contributions of the G2 and D3 residues to the Cx40 channel pore structure, but not with the postulated hydrophobic W4 intermolecular interactions. Our results indicate an absolute requirement for an amphipathic W3/4 residue that is conserved among all α/β/δ/γ-group connexins. We alternatively hypothesize that the connexin D2/3-W3/4 locus interacts with the highly conserved FIFR M1 motif to stabilize the NT domain within the pore.